Severe osteogenesis imperfecta: case report - Fernando Bastos; Liliana Thaureaux Perez; Caridad Ponce de León Narváes; Olívia Costa; Rui Carlos Souto da Silva; Joaquim Carlos Vicente Dias Van-Dunem; Sandra Maria da Rocha Neto de Miranda; Lemuel Bornelli Cordeiro; Patrícia Conceição Silvia Maia; Leonídia de Fátima Lopes Marques Airosa; Aida de Menezes (Einstein (São Paulo), 2010)
The authors present a case of Osteogenesis Imperfecta, emphasizing the clinical and epidemiological characteristics, forms of classification and treatment of the disease. This is an important case not only to the knowledge of pediatricians and orthopedists, but also for other professionals involved with the problem. This article has been jointly described by the Departments of Pediatrics and Neonatology of the Girassol Clinic in Luanda Capital of the Republic of Angola, Africa.